Relationship between aortic root size and glomerular filtration rate in hypertensive patients. Issue 3 (March 2016) - Mulé, Giuseppe; Nardi, Emilio; Morreale, Massimiliano; D'Amico, Salvatore; Foraci, Anna Carola; Nardi, Chiara; Geraci, Giulio; Cerasola, Giovanni; Cottone, Santina
Abstract : Objective: Recent studies suggest that enlarged aortic root diameter (ARD) may predict cardiovascular events in absence of aneurysmatic alterations. Little is known about the influence of renal function on ARD. Our study was aimed to assess the relationships between glomerular filtration rate (GFR) and ARD in hypertensive subjects. Methods: We enrolled 611 hypertensive individuals (mean age: 52 ± 15 years; men 63%). ARD was measured by echocardiography at the level of Valsalva's sinuses using M-mode tracings. It was considered as absolute measure, normalized to body surface area (ARD/BSA) and indexed to height (ARD/H). GFR was estimated by the Chronic Kidney Disease Epidemiology Collaboration equation. The study population was categorized into seven groups: subjects without chronic kidney disease (no CKD) and subjects with increasing severity of CKD (1, 2, 3a, 3b, 4, 5), as proposed by the 2012 Kidney Disease: Improving Global Outcomes guidelines. Results: ARD/BSA and ARD/H showed a stepwise increase from the group with normal renal function to the groups with increasing severity of CKD. GFR correlated significantly with ARD ( r  = –0.17), ARD/BSA ( r  = –0.43) and ARD/H ( r  = –0.35; all P  < 0.001). The associations of GFR with ARD/BSA (β = –0.26; P  < 0.001) and ARD/H (β = –0.13; P  = 0.01) held in linear multiple regression analyses, after adjustment for various confounding factors. Conclusion: Our study seems to suggest that a reduced renal function may adversely influence ARD. This may contribute to explain the enhanced cardiovascular risk associated with renal insufficiency. Abstract : Supplemental Digital Content is available in the text